THE EFFECT OF FEEDBACK ON STUDENT’S WRITING ACCURACY - Asep Suarman (Eltin Journal : Journal of English Language Teaching in Indonesia, 2013)
This paper is concerned with the effect of direct, uncoded oral and writtenfeedback to the writing accuracy. Nine secondary school students, who werechosen purposively from high, mid and low achiever, involved in this study.Observation and document analysis were used to collect data in which errors ofgrammatical - covering subject-verb agreement and clause construction -,lexical and punctuation were analyzed. The result shows that the direct, uncodedoral and written feedback gives significant effect only to the high achievers.But, such feedback does not give much effect to the texts made by midachievers and low achievers. Overall, the feedback does not give significanteffect on the students’ writing accuracy. Considering limitations of the study,some suggestions are also put forward. KEYWORDS: feedback, writing accuracy